Ability To Pay And Willingness To Pay For Covid-19 Vaccination: Are We Ready? - Amirah Azzeri; Nur Amalina Abd Laziz; Muslimah Ithnin; Mohd Hafiz Jaafar (Malaysian Public Health Physicians Association, 2024)
Indexed by Scopus/MyCite